Evaluation of treatment trains to bottled purified water - Arana Muñoz, Omar; Coras Merino, Pablo; Reyes Ramirez, Aurelio (Asuntos Económicos y Administrativos, 2013)
Lately, many companies had entered in the bottle purified water market due to the high profitability showed by this sector. These companies had acquiredequipment that includes, at least, the following processes: filtration, activated carbon, reverse osmosis, ion exchange, ozonation and ultraviolet radiation; some of them unnecessary. The Chapingo Autonomous University bottling plant belongs to this kind of companies. The purpose of this research is to find out which processes are necessary and which are irrelevant to achieve the final goal.The parameters studied were: salinity, in this case, the analysis included pH, electrical conductivity, sodium, potassium, calcium and magnesium cations, chloride, carbonate, bicarbonate and sulphate anions, and NMP coliforms to evaluate pathogens. Each process was studied through different laboratory analyses. The main findings were: Activated carbon, ion exchange and reverse osmosis processes are unnecessary and should be eliminated. Additional benefits will be, the water obtained will contain more minerals very valuable in order to meet human nutritional requirements and better flavor, similar to that of products with significant market share but at a lower price.